Serum Neutrophil Gelatinase-Associated Lipocalin (NGAL) in HCV-Positive Egyptian Patients Treated with Sofosbuvir - Ali Nada; Mohamed Abbasy; Aliaa Sabry; Azza Mohamed Abdu Allah; Somaia Shehab-Eldeen; Nada Elnaidany; Hanan Elimam; Kawthar Ibraheem Mohamed Ibraheem; Abdallah Essa (Canadian Journal of Gastroenterology and Hepatology)
Background. Direct-acting antivirals (DAAs) made a drastic change in the management of HCV infection. Sofosbuvir is one of the highly potent DAAs, eliminated mainly through the kidney. But concerns about renal safety during treatment may limit its use. Neutrophil gelatinase-associated lipocalin (NGAL) has been proven as a predictor of renal tubular injury. Hence, the aim of this work was to assess serum neutrophil gelatinase-associated lipocalin (NGAL) in HCV-positive patients before and after treatment with the sofosbuvir-based antiviral regimen. Methods. This prospective study included 87 Egyptian patients with chronic HCV infection treated with sofosbuvir plus daclatasvir with or without ribavirin for 12 weeks. Serum NGAL was measured before and at the end of treatment (EOT). Analysis of NGAL and estimated glomerular filtration rate (eGFR) evolution was done. Results. Our results showed a statistically significant decrease in serum NGAL (P=0.02) with a nonsignificant reduction in eGFR (P=0.06). Moreover, changes in serum NGAL levels (baseline compared to EOT) in patients ranked by KDIGO-CKD classification showed a significant decrease in stages 1 and 2 (P=0.14 and 0.034, respectively) and a nonsignificant decrease in stage 3 (P=0.25). Also, eGFR changes after treatment in patients ranked by the same classifications showed a nonsignificant reduction in all stages (P>0.05). Conclusions. Sofosbuvir appears to have no nephrotoxic effects and is safe to treat patients with chronic HCV infection.